1999
DOI: 10.4141/p98-113
|View full text |Cite
|
Sign up to set email alerts
|

Crop density and seed production of tall fescue (Festuca arundinacea Schreber). 2. Reproductive components and seed characteristics

Abstract: Fairey, N. A. and Lefkovitch, L. P. 1999. Crop density and seed production of tall fescue (Festuca arundinacea Schreber). 2. Reproductive components and seed characteristics. Can. J. Plant Sci. 79: 543-549. The population density and spatial arrangement of plants may influence the productive life and performance characteristics of a perennial grass-seed crop. A study was conducted to determine the effects of the initial density (1.6, 3.1, 6.3, 12.5, 25, 50 and 100 plants m -2 ) and row spacing (20, 40, and 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Except in the case of spaced rows, such as grass grown for seed production (Young et al. , 1998; Fairey and Lefkovitch, 1999), there is little information on the density, proportion and dynamics of fertile tillers (Watson and Watson, 1982; Hume and Brock, 1997). Even less is known about the fine‐scale spatial distribution of tillers (Herben et al.…”
Section: Introductionmentioning
confidence: 99%
“…Except in the case of spaced rows, such as grass grown for seed production (Young et al. , 1998; Fairey and Lefkovitch, 1999), there is little information on the density, proportion and dynamics of fertile tillers (Watson and Watson, 1982; Hume and Brock, 1997). Even less is known about the fine‐scale spatial distribution of tillers (Herben et al.…”
Section: Introductionmentioning
confidence: 99%
“…and perennial ryegrass (Lolium perenne L.), SYs were highest with sowing rates of 20 kg ha −1 (.4 g m −1 of row length). The effect of row spacing on tall fescue seed production has been investigated in the US and Canada (Fairey & Lefkovitch, 1999a, 1999bYoung et al, 1998aYoung et al, , 1998b. Row spacing studies also have been conducted in separate climates on red fescue (Festuca rubra L. var.…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%
“…A study evaluating SR and RSW effects on annual ryegrass indicated that SR can have significant positive effects on yield during growing seasons with unfavorable weather conditions that result in less biomass growth (Simic et al, 2009). When determining SRs that provide optimal plant density (or vegetative cover), it is important to consider loss of seedlings during establishment (Fairey and Lef kovitch, 1999b) so the effect of SR on EVC at the 20-and 30-cm RSW should be evaluated following more harsh winters. The overall greater EVC and greater response to SR at the 10-cm RSW suggests that the 10-cm RSW is optimal for promoting greater EVC in the environments tested here, which may be due to less within-row plant competition (Deleuran et al, 2009;Deleuran et al, 2010).…”
Section: Early-season Vegetative Covermentioning
confidence: 99%